A GEOTECHNICAL STUDY ON THE CHARACTERISTICS OF SWELL-SHRINK SOILS IN KIBAHA, TANZANIA - Lucian, Charles; Hintze, Staffan; Msambichaka, Joseph J (Tanzania Journal of Engineering and Technology, 2018)
The properties of Swell-shrink of the soils in Kibaha were studied. Geotechnical and mineralogical tests were carried out on disturbed and undisturbed samples recovered from trial pits at different locations. Using empirical relationships, the swelling potential of the soil was established in correlation with the soil plasticity limits and grain size analysis (clay contents). The average values for the plastic, liquid and linear shrinkage limits for soils were 22.2%, 60.7% and 14.5% respectively. The plasticity Index (PI) which is the difference between liquid limits and plastic limits ranges from 27% to 47.4% with an average of 38.5%. The natural water content is very small ranging from 7% to 11% with an average of 9.6% which is smaller than the corresponding shrinkage limit. Furthermore, the samples were tested for percentage of volume change in free swell tests and swelling pressure in one- dimensional swell tests. The free swell and upward pressure were in the excess of 100% to 150% and 50 kPa respectively. In addition, the coefficient of linear extensibility ranged from 0.09 to 0.14 signifying high to very high swell- shrink potential. Finally, the main clay mineral present in the sample was determined by running the X-ray diffraction (XRD) test. The x- ray diffraction scan indicated the presence of high proportion of clay minerals (smectite) in the soils.